Hemostatic Agents for Bleeding: Recombinant-Activated Factor VII and Beyond - Franchini, Massimo; Crestani, Silvia; Frattini, Francesco; Sissa, Cinzia; Bonfanti, Carlo (Seminars in Thrombosis and Hemostasis, 2015)
A rapid restoration of hemostasis should be regarded as a primary goal for management of critical bleeding, which often represents a life-threatening condition. Among the various therapeutic strategies available in this clinical setting, we aim to summarize in this narrative review the current status on the use of recombinant-activated factor VII and prothrombin complex concentrates. The safety and effectiveness of these hemostatic agents in reversal of the anticoagulant effects of vitamin K antagonists will be also explored. In addition, their role in the management of acute bleeding associated with the newer direct oral anticoagulants dabigatran, rivaroxaban, and apixaban will be analyzed in a dedicated section.
Keywords: rFVIIa; prothrombin complex concentrates; bleeding; warfarin; vitamin K antagonists; new oral anticoagulants